“Selective cell death mediated by small conditional RNAs” is not selective - Patel, Kalpesh (Landes Bioscience, 2013)
Small conditional RNAs were used to kill cells selectively in a prior report. The method utilized the cellular innate immune response to dsRNA, causing PKR activation and cell death. We designed small conditional RNAs specific to a highly restricted transcript, that of the mesothelin gene expressed in various cancer lines and specific to a tpc/hpr fusion transcript expressed in a published “control” line. Hairpins of small conditional RNAs were functionally active in cell-free conditions. Hairpins were transfected into 6 types of cells. We observed non-specific killing of cells after transfection of the hairpins targeting the reported fusion transcript or of the mesothelin transcript. Thus when attempting to use this system for a special purpose, to target cancer mutations, the results were not satisfactory. Specifically when repeating the work described in the publication, we could not replicate the results using the methods described. Recently the publication was retracted but without comment on the validity of the reported method. Here we provide scientific basis to consider the method impaired or invalid.